Peningkatan Hasil Belajar Siswa melalui Media Vidio Pembelajaran PAI Kelas V SDN 05 Situjuah Gadang - Victoria Lilian; Iswantir Iswantir; Defi Yuslia; Amrina Amrina; Desi Wirya; Peta Mayurida (Jurnal Pendidikan Tuntas, 2024)
This study aims to improve the learning outcomes of Islamic Education (PAI) through the use of instructional video media for fifth-grade students at SDN 05 Situjuah Gadang. This is classroom action research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection phases. The research subjects were 10 fifth-grade students. Data were collected through learning outcome tests and observations of student activities during the learning process. The results show an improvement in student learning outcomes. In the pre-cycle, only 35% of students achieved mastery with an average score of 74. After the action was implemented in the first cycle, mastery increased to 55% with an average score of 77. In the second cycle, the percentage of students achieving mastery significantly increased to 85% with an average score of 85. This improvement demonstrates that the use of instructional video media is effective in enhancing student learning outcomes, especially in motivating students and facilitating the understanding of the concepts being taught. Overall, this research proves that instructional video media can be an effective tool to improve the quality of learning, particularly in Islamic Education subjects. Keywords:,,,